2016
DOI: 10.1016/j.oceaneng.2016.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Vortex shedding suppression and wake control: A review

Abstract: Wake destructive behavior and vortex shedding behind bluff bodies may be controlled by use of active and passive methods. Computational fluid dynamics, experimental and analytical techniques have been utilized to study this problem. In this survey, existing studies on different methods of controlling the wake destructive behavior and suppression of vortex shedding behind bluff bodies are discussed, including the very recent developments. These methods are classified into two groups. In the first group, these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(56 citation statements)
references
References 164 publications
(62 reference statements)
0
45
0
Order By: Relevance
“…The passive methods depend on modifications of the bluff body geometry, which affect the formation of the vortex shedding. The active control methods need external energy to affect the fluid flow [11,33].…”
Section: Introductionmentioning
confidence: 99%
“…The passive methods depend on modifications of the bluff body geometry, which affect the formation of the vortex shedding. The active control methods need external energy to affect the fluid flow [11,33].…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the structure experiences unsteady loading due to flow separation and formation of the vortices and the wake region. There are several approaches to reduce VIV, see, e.g., Rashidi et al (2016).…”
Section: Ballast-stabilised Platformsmentioning
confidence: 99%
“…Dhinakaran and Ponmozhi [ 8 ] found that compared to that for a solid cylinder, a considerable heat transfer increment was achieved for a permeable cylinder, since more fluid passed through the porous cylinder, carrying more heat away. Besides, a porous medium provides an ability of controlling the flow characteristics and suppressing the formation of vortex shedding [ 9 ]. For example, Al-Sumaily and Thompson [ 10 ] found that for pulsatile flow over a circular cylinder in a channel with the presence of the porous media, a highly stable flow occurs without the formation of the extended wake in the flow field.…”
Section: Introductionmentioning
confidence: 99%